Activity of Sorafenib Plus Capecitabine in Previously Treated Metastatic Colorectal Cancer. (22nd February 2021) - George, Thomas J.; Ivey, Alison M.; Ali, Azka; Lee, Ji‐Hyun; Wang, Yu; Daily, Karen C.; Ramnaraign, Brian H.; Tan, Sanda A.; Terracina, Krista P.; Read, Thomas E.; Dang, Long H.; Iqbal, Atif
Abstract: Lessons Learned : Treatment for patients with metastatic colorectal cancer (mCRC) typically involves multiple lines of therapy with eventual development of treatment resistance. In this single‐arm, phase II study involving heavily pretreated patients, the combination of sorafenib and capecitabine yielded a clinically meaningful progression‐free survival of 6.2 months with an acceptable toxicity profile. This oral doublet therapy is worthy of continued investigation for clinical use in patients with mCRC. Background: Capecitabine (Cape) is an oral prodrug of the antimetabolite 5‐fluorouracil. Sorafenib (Sor) inhibits multiple signaling pathways involved in angiogenesis and tumor proliferation. SorCape has been previously studied in metastatic breast cancer. Methods: This single‐arm, phase II study was designed to evaluate the activity of SorCape in refractory metastatic colorectal cancer (mCRC). Patients received Sor (200 mg p.o. b.i.d. max daily) and Cape (1, 000 mg/m 2 p.o. b.i.d. on days 1–14) on a 21‐day treatment cycle. Primary endpoint was progression‐free survival (PFS) with preplanned comparison with historical controls. Results: Forty‐two patients were treated for a median number of 3.5 cycles (range 1–39). Median PFS was 6.2 (95% confidence interval [CI], 4.3–7.9) months, and overall survival (OS) was 8.8 (95% CI, 4.3–12.2) months. One patient (2.4%) had partial response (PR), and 22 patients (52.4%) had stable disease (SD) for a clinical benefit rate of 54.8% (95% CI, 38.7%–70.2%). Hand‐foot syndrome was the most common adverse event seen in 36 patients (85.7%) and was grade ≥ 3 in 16 patients (38.1%). One patient (2.4%) had a grade 4 sepsis, and one patient (2.4%) died while on treatment. Conclusion: SorCape in this heavily pretreated population yielded a reasonable PFS with manageable but notable toxicity. The combination should be investigated further.